Distributing digital imaging and communications in medicine data and optimizing access over satellite networks...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Ernst RD; Kawashima A; Shepherd W; Tamm EP; Sandler CM (Journal of Digital Imaging)
To improve radiology access to full uncompressed Digital Imaging and Communications in Medicine (DICOM) data sets, we evaluated satellite access to a DICOM server. Radiologists' home computers were connected by satellite to a Medweb DICOM server (Medweb, San Francisco, CA). A 10.2-kb data set containing a 19-image head computed tomography (CT) scan was transferred using DirecPC (Hughes Electronics Corp, Arlington, VA) at three different times of the day; 6 AM, 3 PM, and 8 PM. The average transfer time for all 19 images from the DICOM server was 4 minutes and 17 seconds (257 seconds). The slowest transfer rate of 670 seconds (121 kbps) was obtained at 8 PM. The best transfer rate of 2 minutes, 54 seconds (467 kbps) was obtained at 6 AM. The full 16-bit DICOM images were viewed with bone, brain, and soft tissue windows. The Medweb plug-in viewer loaded the first image within 30 seconds of selecting the case for satellite transfer. In conclusion, satellite internet transfer of radiology studies is suitable for timely review of full DICOM data sets and can expand the range of teleradiology consultation. Copyright (c) 1999 by W.B. Saunders Company